(untitled) (Comprehensive Journal of Science, 2025)
This study aims to evaluate the impact of temperature and aging time on the performance of open asphalt mixtures, using the "Cantabro" test, which is one of the essential tests for determining the resistance of mixtures to wear and disintegration. This study contributes to improving the design of open asphalt mixtures, enhancing their efficiency in water drainage, reducing slippage, and improving traffic safety, especially in areas with harsh environmental conditions. The study was conducted on samples taken from the coastal road in the Qasr al-Akhyar area of Libya, where the samples were divided into three groups: non-aged samples, samples subjected to thermal aging at a temperature of 85°C for 5 days, and samples subjected to thermal aging at a temperature of 85°C for 7 days. One of the main findings is that the non-aged samples showed the lowest weight loss compared to the other groups, indicating a negative effect of thermal aging on asphalt mixtures. The percentages of air voids and aggregate increased with rising temperatures and aging duration, indicating the disintegration of the asphalt mixture structure. The percentage of voids filled with asphalt decreased with increasing temperatures due to the evaporation of light asphalt components and oxidation, leading to a decline in mixture efficiency. Thermal aging negatively affects the performance of open asphalt mixtures, resulting in increased wear, disintegration of aggregates, and reduced cohesion among components. Additionally, high temperatures reduce the mixture’s ability to resist environmental factors such as moisture and cracking.